ANALISIS PROFITABILITAS PADA INDUSTRI BARANG KONSUMSI DI BURSA EFEK INDONESIA - Wehelmina M Ndoen (Journal of Management Small and Medium Enterprises (SME's), 2019)
This research aims to investigate the Return On Investment (ROI), Return On Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS) of Consumer Goods Industry in Indonesia Stock Exchange year 2013-2015. The samples are 12 companies determined by purposive sampling technique. Results obtained that the ROI, ROE, NPM and EPS can not be the tool of decision for investors because of the fluctuation results in year 2013-2015